2015
DOI: 10.1016/j.jat.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

A family of nonlinear difference equations: Existence, uniqueness, and asymptotic behavior of positive solutions

Abstract: We study solutions pxnq nPN of nonhomogeneous nonlinear second available online: MMM DD, 2014. 2010 Mathematics Subject Classification. 39A22, 65Q10, 65Q30. Key words and phrases. nonhomogeneous nonlinear second order difference equations, Shohat-Freud-type exponential weight functions, Painlevé's discrete equation #1, existence of solutions, unicity of solutions, asymptotic behavior.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Lew and Quarles [13], Nevai [16], and Bonan and Nevai [3] showed that there exists a unique solution of (1.6) with x 0 = 0 for which x n > 0 for all n ≥ 1 and this solution corresponds to x 1 = 2Γ( 3 4 )/Γ( 1 4 ). This result was recently also proved for a family of non-linear recurrence relations generalizing (1.6), see [1].…”
Section: Introductionmentioning
confidence: 65%
“…Lew and Quarles [13], Nevai [16], and Bonan and Nevai [3] showed that there exists a unique solution of (1.6) with x 0 = 0 for which x n > 0 for all n ≥ 1 and this solution corresponds to x 1 = 2Γ( 3 4 )/Γ( 1 4 ). This result was recently also proved for a family of non-linear recurrence relations generalizing (1.6), see [1].…”
Section: Introductionmentioning
confidence: 65%
“…The existence of β 1 (t; λ) > 0 such that (5.2) is a positive sequence follows immediately from [2,Thm. 4.1].…”
Section: Existence and Uniqueness Of Positive Solutionsmentioning
confidence: 89%
“…Several papers, including [38,52,61] provide an answer for the case where t = 0. In a recent paper by Alsulami et al [2], existence and uniqueness of a positive solution are discussed for the nonlinear second-order difference equations of the type β n (σ n,1 β n+1 + σ n,0 β n + σ n,−1 β n−1 ) + κ n β n = n (5.1)…”
Section: Existence and Uniqueness Of Positive Solutionsmentioning
confidence: 99%
“…In the paper [1], Alsulami et al discussed the existence and uniqueness of a positive solution for the nonhomogeneous nonlinear second order difference equations of the form, n = x n (σ n,1 x n+1 + σ n,0 x n + σ n,−1 β n−1 ) + κ n x n (7.1)…”
Section: Existence Uniqueness Of Positive Solutionsmentioning
confidence: 99%
“…with the initial conditions x 0 ∈ R, x 1 ≥ 0, whilst κ n ∈ R, σ n,j > 0, j ∈ {0, ±1}, or {σ n,0 > 0, σ n,−1 ≥ 0, σ n,1 ≥ 0}. Following the results presented in [1], the solution of Eq. (4.9) is obtained.…”
Section: Existence Uniqueness Of Positive Solutionsmentioning
confidence: 99%